ANALISIS KESESUAIAN LAHAN UNTUK KAWASAN PENDIDIKAN DI KABUPATEN MAJALENGKA - Harun Din Haq; Khairunnisa Susilo (REKSABUMI, 2023)
Educational area has a characteristic educational function that supports the improvement of knowledge, physical, and morals so that students can achieve their highest goals and ideals. The Educational Area of Majalengka Regency is the border point of 3 villages and 1 kelurahan, namely Panyingkiran Village, Jatipamor Village, Jatisawit Village, and Majalengka Village, and the border of 3 sub-districts namely Panyingkiran District, Kasokandel District, and Majalengka District. The Majalengka Regency Education Area, which is planned to use the healthy learning landscape concept, needs to be analyzed for the suitability of the land and whether the supporting activities can support the main educational activities. The purpose of this study is to analyze the suitability of the land around the construction site of the Politeknik Manufaktur Campus so that the area supporting educational activities there is in accordance with the carrying capacity and capacity of the land. The land suitability analysis used is an overlay analysis using the weighting point method. The result is that there are 4 suitability classes, which are not in accordance with the results of score 2 covering an area of 30.4 ha (39.01% of the total area), then quite in accordance with the results of score 3 covering an area of 25.38 ha (32.57% of the total area). , then in accordance with the results of score 4 covering an area of 20.03 ha (25.70% of the total area) and very much in accordance with the results of score 5 covering an area of 2.12 ha (2.72% of the total area).